Do Vietnamese schools provide the right education for an industrialising country? - Baulch, B; Dat, V; Thang, N (Young Lives, 2012)
This paper examines whether Vietnamese schools are providing children with the education that is needed by an industrialising middle-income country. International comparisons show that, despite Vietnam’s generous spending on education, the country’s school enrolments and attainments are relatively low compared to its competitors in east and south-east Asia. The 2007 Labour Force Survey is used to examine the qualifications that new labour market entrants need to obtain skilled employment, and to investigate the returns to different levels of education. The results suggest that there is currently not a strong demand in manufacturing for workers with either professional or tertiary education. Labour market entrants with post-secondary qualifications earn manufacturing wages that are, on average, only 40 to 50 per cent higher than workers with primary education. This is consistent with the relatively routine nature of most jobs in manufacturing, which has focused on products which can be produced by assembly line workers with limited schooling. Finally, Rounds 2 and 3 of the Young Lives data are used to investigate which children are being left behind by the education system. A small but significant group of children who are failing to complete lower secondary school, and are therefore very unlikely to gain wage employment in the manufacturing or government sectors, is identified.